Food industry SMEs in France, uses of new technologies for internationalisation - Doron, Bruno (2014)
Internationalisation of small and medium enterprises (SMEs) is a well-studied field of research that have the interests of both the scientific community and policy makers. Since the beginning of the global financial crisis in 2008, France import and export balance is badly in deficit. In an attempt to solve this issue, the French government is offering intensive support for SMEs to export their goods. This dissertation is examining the different stages of internationalisation for French food industry SMEs and more specifically, how technology can help to overcome challenges of internationalisation for SMEs. This dissertation reviewed the existing researches done on SME’s internationalisation and technology usages in SMEs. Following this review, the topic of technology usages in international SMEs is investigated (focusing on information and communication technology; enterprise resource planning). For the collection of primary data, a set of ten companies has been purposively selected. Each company was interviewed during an average of forty-five minutes in a semi-structured manner. A thematic analysis was done and the findings are presented and discussed at the end of this dissertation. It was found that SMEs of the food industry often seized opportunity to start their international activities with the help of a new relationship in their network. Regarding the use of technologies, all companies were primarily focused on production technologies, regardless of their size. With the size of the SME growing, the use of ICT and ERP become systematic and more intensive.